2000
DOI: 10.1002/1097-0088(200012)20:15<1899::aid-joc588>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature anomalies on the Palmer Drought Severity Index in the central United States

Abstract: The purpose of this study is to improve our understanding of temperature and precipitation effects on the Palmer Drought Severity Index (PDSI). Both theoretical and observational analyses were applied to separate and compare temperature and precipitation effects on PDSI. The results showed that because of the dependence of PDSI on the ‘climatologically appropriate rainfall’, which is a function of time and varies with surface air temperature, the PDSI can be equally affected by temperature and precipitation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 16 publications
1
58
0
1
Order By: Relevance
“…This demonstrates that the variability of the temperature would have a remarked impact on the drought severity on the Loess Plateau during the time span from 1954 to 2012. Hu and Willson (2000) also found that temperature anomalies play a crucial role in explaining the drought variability in central United States, and it could be comparable to the role of precipitation under some circumstances. The effects of temperature on drought severity should be attributed to its direct impact on evapotranspiration (Sheffield and Wood, 2008) and the follow-up impacts on runoff, river discharge, groundwater and reservoir water storage (Zipper and Loheide II, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…This demonstrates that the variability of the temperature would have a remarked impact on the drought severity on the Loess Plateau during the time span from 1954 to 2012. Hu and Willson (2000) also found that temperature anomalies play a crucial role in explaining the drought variability in central United States, and it could be comparable to the role of precipitation under some circumstances. The effects of temperature on drought severity should be attributed to its direct impact on evapotranspiration (Sheffield and Wood, 2008) and the follow-up impacts on runoff, river discharge, groundwater and reservoir water storage (Zipper and Loheide II, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…The trend analysis of SPI magnitude showed a decreasing tendency, indicating increasing drought, which is more evident at the longer time scale. Even there is limited study concerning drought trend in Nepal, evidence of increased occurrence of drought due to precipitation deficit is consistent with the results presented by previous researchers (Kafle 2014;Sigdel and Ikeda 2010;Wang et al 2013) Several studies (Chang and Kleopa 1991;Heim 2002;Paulo and Pereira 2006) have shown that precipitation is the main variable determining drought condition; however, many empirical studies (Hu and Willson 2000;Rebetez et al 2006;Vicente-Serrano et al 2009) Nat Hazards (2016) 80:1913-19321927 have shown that rise in temperature has important effects on the severity of droughts conditions. Figure 12 shows that there is increasing trend of temperature in all region of central Nepal in past.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have warned against systematically neglecting the importance of the effect of temperature on drought conditions. For example, Hu and Willson (2000) assessed the role of precipitation and temperature in the PDSI, and found that the index responded equally to changes of similar magnitude in both variables. Only where the temperature fluctuation was smaller than that of precipitation was variability in the PDSI controlled by precipitation.…”
mentioning
confidence: 85%